Pembelajaran Kitab Kuning di Pondok Pesantren (Pembelajaran kitab kuning di pondok pesantren Al-Lathifiyah 2 Bahrul 'Ulum Tambakberas Jombang) - Rohmah, Khalimatur (Al-Tadris: Jurnal Pendidikan Bahasa Arab, 2022)
تدريس كتب الصفراء أمر مهم في تعليم المعهد بسبب هذا الكتاب حجة وأساس. يجب مراعاة تنفيذ التعلم فيما يتعلق بالأساليب والطريقة المستخدمة حتى يمكن تحقيق أهداف التعليم. وكذلك التقويم. يجب أيضًا مراعاة نموذج التقويم المستخدم في اختبار كفاءةالطلاب أثناء دراسة كتب الصفراء, حيث يعرف المعلمون مدى فهم الطلاب للمواد التي يتم تدريسها. هدف هذه الدراسة إلى تقديم لمحة عامة عن معنى قراءة الكتاب الأصفر وتنفيذ تدريس كتب الصفراء وتقويمه في تدريس كتب الصفراء. Teaching yellow books is important in the education of the institute because of this book as an argument and basis. The implementation of learning must be considered in relation to the methods and method used so that the learning objectives can be achieved. So is the calendar. The evaluation form used to test students' aptitude should also be taken into account while studying yellow books, as teachers know how well students understand the material being taught. The aim of this study is to provide an overview of the meaning of reading the yellow book and the implementation of teaching yellow books and its evaluation in teaching yellow books